High-dose atorvastatin ameliorates the uterine microenvironment in streptozotocin-induced diabetic rats. (November 2014) - Zeybek, Burak; Ergenoglu, Mete; Erbas, Oytun; Yildirim, Nuri; Akdemir, Ali; Yavasoglu, Altug; Aktug, Huseyin; Taskiran, Dilek
Abstract The aim of this study was to investigate whether atorvastatin can ameliorate the uterine microenvironment in diabetes mellitus. Six non-diabetic (control) and 12 diabetic mature female Sprague–Dawley albino rats were used in this study. Diabetes was induced by intraperitoneal injections of 60 mg/kg streptozotocin, and 10 mg/kg/day of oral atorvastatin was administered for 4 weeks via orogastric tubes. The animals were euthanized, and blood samples were collected via cardiac puncture for biochemical analysis. Bilateral hysterectomy was performed for the histopathologic examination. Endometrial gland degeneration and stromal fibrosis scores concomitant with epidermal growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) immunoexpressions were analyzed. The endometrial gland degeneration scores, stromal fibrosis scores and VEGF immunoexpression was significantly lower, and the EGFR immunoexpression was significantly higher in the atorvastatin-treated diabetic rats when compared to the non-treated diabetic group, suggesting that atorvastatin ameliorates the uterine microenvironment in diabetes mellitus.